PENGARUH MEDIA PEMBELAJARAN KARTU KWARTET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS IV SDN 101782 TANJUNG REJO - Harahap, Bahani Permata; Dahnial, Irfan (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
This study aims to see the effect of Quartet Card Learning Media on Student Learning Outcomes in Social Studies Subjects in Class IV SDN 101782 Tanjung Rejo. The research subjects were 21 fourth grade students of SDN 101782 Tanjung Rejo. The method used is Pre-Experimental type experiment using One Group Pretest-Posttest. The instrument used in this research is a multiple choice test, with a total of 20 questions. The data was analyzed through the paired sample t test, based on the results of the t test obtained a sig value. (2-tailed) 0.000 < 0.05, meaning that the alternative hypothesis () is accepted. Thus, it can be concluded that the application of quartetcard media has a significant effect on student learning outcomes in social studies lessons in class IV SDN 101782 Tanjung Rejo. Thus, it can also be recommended to teachers to be applied during learning.